A Feasibility analysis of cement-bonded boards using Pili nutshells - Alberto, Raymund; Ayes, Sheryl; Dompor, Ma. Lorena (Diliman, Quezon City College of Engineering, 2002)
Fueled with the growth of the construction sector, and the general demand for housing in the country, the presence of cement-bonded boards as an alternative paneling materials have been recognized. This feasibility study addresses the production of cement-bonded using pili nutshells as the base material together with cement. The study period is set at five (5) years. The market analysis determines the demand for paneling and its determinants. It was found that the demand for paneling and boards is continuously increasing for the next ten years. The projected supply of paneling showed that it would not be able to support the demand in the coming years given an adequate gap for the introduction of the product in to the market. The initial market was set to Reg. 3, Reg. 4 and the NCR. A marketing strategy and market mix was proposed, to support the market feasibility of the product The technical feasibility of the product was then established. This was done through analysis of the production process, raw materials sourcing, and the acquisition of plant equipment. The production process would be divided into the pre-production and the production phase. Which is further subdivided to the production operations. The number of machines was determined using capacity planning, and the location and layout of the facility was also presented. The firm will utilize the partnership form of ownership to lessen the effect of double-taxation inherent to corporations and the large risk involved in sole proprietorship. The financial analysis presented the method of financing of the project which involves a 70-30 division of the total project cost; 70% will be shouldered by three partners, while the remaining 30% will be funded through a 5-year loan. The financial viability of the project, and further reinforced using the break-even point, and the net present value. The social profitability analysis presented the benefits and advantages that the project brings to the society and its environment. All in all, it was determined and established that Cement-bonded boards using Pili nutshells is a feasible venture.
IE 153
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Cement industries; Cement composites; Pili nut; Participatory monitoring and evaluation (Project management)